2009
DOI: 10.2298/jsc0911241m
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, volatiles and antibacterial screening of lipids of the sponge Fasciospongia cavernosa (Schmidt) collected from the bay of Bengal (Orissa coast)

Abstract: The fatty acid composition as well as the volatiles of a lipophilic extract from the marine sponge Fasciospongia cavernosa (Schmidt) was analyzed. The fatty acids (FA) were characterized by linear saturated fatty acids (33.05 %), branched saturated fatty acids (9.30 %) and mono-unsaturated fatty acids (18.07 %). A significant amount of polyunsaturated fatty acids (PUFA) (30.79 %) was found in the total lipid, which included linoleic acid (18:2 n-6, 11.14 %), 9,12,15-octadecatrienoic acid/?-linolenic acid (18:3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…2-Methylbutyryl-carnitine, a short chain acylcarnitine, is produced by many eukaryotes, including sponges [ 69 ]. Eicosatrienoic acid methyl ester is an isomeric, methylated derivative of dihomo-γ-linolenic acid, which has been previously found in the sponge Fasciospongia cavernosa [ 70 ] and might be involved in host defense and immunity [ 71 , 72 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2-Methylbutyryl-carnitine, a short chain acylcarnitine, is produced by many eukaryotes, including sponges [ 69 ]. Eicosatrienoic acid methyl ester is an isomeric, methylated derivative of dihomo-γ-linolenic acid, which has been previously found in the sponge Fasciospongia cavernosa [ 70 ] and might be involved in host defense and immunity [ 71 , 72 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…They all confront bacteria through several mechanisms of action, all of which primarily involve the perturbation of bacterial cell membrane [29]. The bactericidal activity of LCUFAs against S. aureus enhanced with increasing degree of unsaturation [12]. PL includes phospholipids which are richer in LCUFAs due to their functional role [30].…”
Section: Discussionmentioning
confidence: 99%
“…Given that PAF is an initial trigger in atherosclerosis [11], foodstuffs, which exert antibacterial activities, suppress the production of PAF, and therefore play a positive role in preventing atherosclerosis. Previous studies have demonstrated the lipids extracted from red shrimp brain, marine sponge, sea bass and gilthead sea bream exerted antibacterial activities [10,12,13]. Besides, antimicrobial agents have been prepared from the lipids of marine fishes [14].…”
Section: Introductionmentioning
confidence: 99%